The development of stress sensitivity and its contribution to word reading in school‐aged children. (27th December 2016) - Lin, Candise Y.; Wang, Min; Newman, Rochelle S.; Li, Chuchu
Abstract : Background: This study examined the development of stress sensitivity and its relationship with word reading. Previous research has rarely measured phoneme and stress sensitivity in the same task, making a direct comparison of the contribution between the two in reading development difficult. Methods: Participants were native English‐speaking adults and children at ages of 6, 8, and 10 years ( N = 24, 22, 22, and 24, respectively). A lexical decision task was used to measure both stress and phoneme sensitivity. Oral vocabulary, phoneme awareness, and word reading were assessed. Results: Stress sensitivity accounted for unique variance in reading over and above vocabulary and phoneme awareness in 6‐year‐olds. Both adults and children had better phoneme sensitivity than stress sensitivity. Conclusions: These findings highlight the unique contribution of stress sensitivity in reading development. The current study made a novel contribution to studying the relationship between prosody and literacy by utilising a task that is able to assess children's stress and phoneme sensitivity simultaneously. What is already known about this topic Prosody plays an important role in literacy acquisition across a variety of languages with word stress. Phoneme awareness as measured by the phoneme deletion task is one of the strongest predictors of reading development in English. Stress sensitivity may contribute to reading via vocabulary development, rime awareness, phoneme awareness, and morphological awareness. What this paper adds Stress sensitivity made a unique contribution to word reading over and above oral vocabulary and phoneme awareness for 6‐year‐old children. Both stress and phoneme sensitivity was measured within the same task using the same set of materials. Both children and adults showed better phoneme sensitivity compared to stress sensitivity. Implications for theory, policy, or practice Models delineating the relationship between prosody and literacy should consider unique variance explained by stress sensitivity in reading development. Children learning to read in English may need longer literacy exposure to develop better stress sensitivity because of the lack of regularity in English stress. Stress sensitivity may contribute to word reading given that it may help children understand stress assignment and learn unfamiliar stress representation as well as orthographic stress regularities.